2012
DOI: 10.1002/cbdv.201100073
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Certain Taxonomic and Environmental Parameters on Biomass Production and Triterpenoid Content in the Leaves of Centella asiatica (L.) Urb. from Madagascar

Abstract: Centella asiatica (Apiaceae family; Talapetraka in Malagasy) is a tropical and subtropical plant with leaves containing glycotriterpenoids (asiaticosides) used in traditional and modern medicine. C. asiatica is collected exclusively in natural stands. It is Madagascar's second most important indigenous plant export. The objective in this study is to provide data which will make it possible to optimize the harvest and thus effectively develop this resource. Two foliar morphotypes were identified: morphotype A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Samples with the highest content of both asiaticoside and total triterpenes originated from regions with elevated humidity and temperature (Randriamampionona et al ., ). Another Madagascan study reported a correlation of biomass yield and the asiaticoside content which were high during the rainy season and low during the dry season (Rahajanirina et al ., ), although the influence of temperature was not clear.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Samples with the highest content of both asiaticoside and total triterpenes originated from regions with elevated humidity and temperature (Randriamampionona et al ., ). Another Madagascan study reported a correlation of biomass yield and the asiaticoside content which were high during the rainy season and low during the dry season (Rahajanirina et al ., ), although the influence of temperature was not clear.…”
Section: Resultsmentioning
confidence: 97%
“…Higher yields of both, biomass (79.9 ± 1.5 g dry matter/m 2 ) and asiaticoside (5.8%) were found during the rainy season and lower biomass yield (15.1 ± 0.7 g dry matter/m 2 ) and asiaticoside (2.7%) were found during the dry/cold season. (Rahajanirina et al ., ). The influence of seasonal changes in the accumulation of phytochemical constituents can contribute differentially according to the geographical location.…”
Section: Introductionmentioning
confidence: 97%
“…As humidity and temperature elevated, samples exhibited the highest content of both asiaticoside and total triterpenes [ 104 ]. Another study reported the content of asiaticoside was higher during the rainy season and lower during the dry season [ 105 ]. More vividly, the effect of soil water on the content of plant secondary metabolites is displayed in Table 5 .…”
Section: Response Of Plant Sms To Soil Watermentioning
confidence: 99%
“…Twelve C. asiatica accessions collected from multiple regions of South Africa had asiaticoside levels ranging from 0.75% to 2.06% dry weight (Long et al 2012). A study in Madagascar compared triterpene levels in two C. asiatica morphotypes, reniform leaves (type A; n=32 collection sites) and round leaves (type B; n= 13 collection sites), from the Eastern and Western regions of the island respectively (Rahajanirina et al 2012). Type A plants were found to have significantly higher levels of asiaticoside (3.7% vs 2%) and madecassoside (3.6% vs 2%) than the Type B plants, although aglycone levels did not differ significantly.…”
Section: Phytochemistrymentioning
confidence: 99%